Rotational Isomerism in Acetic Acid: The First Experimental Observation of the High-Energy Conformer - Maçôas, Ermelinda M. S. (2003)
The high-energy conformer of acetic acid (cis-AA) is produced in an Ar matrix by vibrational excitation of the OH stretching overtone of the ground conformational state (trans-AA). IR-absorption spectroscopy provides a clear identification of the reaction product. cis-AA converts back to trans-AA in a time scale of minutes at 8 K by tunneling.